Translation in Chile 50 Years After the Beginning of the Training of Professional Translators and 30 Years After the Creation of the Chilean Association of Translators and Interpreters - Poblete-Poblete, M (PONTIFICIA UNIV CATOLICA CHILE, FAC LETRAS, 2022)
In the context of celebrating 50 years of translator training and 30 years since the creation of the Chilean Association of Translators and Interpreters - Cotich, the purpose of this article is to describe the present situation of the training of translators, to present an historical overview of the research initiatives in the discipline, and to expose some professional, trade union and legal characteristics of the practice of translation in our country. First, we describe the transla- tor training offered by universities and professional institutes as of the year 2020, followed by a summary of the development of research on translation and related areas since the mid-1980s. Secondly, we describe the work carried out by Cotich as a professional association, the features of the labor market, and some professional aspects that characterize legal translation in Chile. We end the analysis with a discussion of the data, considering its historical evolution over the last 50 years and some future projections. This general overview of translation, since the be- ginning of its institutionalization process in the early 1970s, may contribute to the training of translators, and serve as a reference tool for students, academics, and professional translators.